Coronary CT angiography with single-source and dual-source CT: Comparison of image quality and radiation dose between prospective ECG-triggered and retrospective ECG-gated protocols - Sabarudin, Akmal; Sun, Zhonghua; Yusof, A. (Elsevier, 2013)
Background This study is conducted to investigate and compare image quality and radiation dose between prospective ECG-triggered and retrospective ECG-gated coronary CT angiography (CCTA) with the use of single-source CT (SSCT) and dual-source CT (DSCT). Methods A total of 209 patients who underwent CCTA with suspected coronary artery disease scanned with SSCT (n = 95) and DSCT (n = 114) scanners using prospective ECG-triggered and retrospective ECG-gated protocols were recruited from two institutions. The image was assessed by two experienced observers, while quantitative assessment was performed by measuring the image noise, the signal-to-noise ratio (SNR) and the contrast-to-noise ratio (CNR). Effective dose was calculated using the latest published conversion coefficient factor. Results A total of 2087 out of 2880 coronary artery segments were assessable, with 98.0% classified as of sufficient and 2.0% as of insufficient image quality for clinical diagnosis. There was no significant difference in overall image quality between prospective ECG-triggered and retrospective gated protocols, whether it was performed with DSCT or SSCT scanners. Prospective ECG-triggered protocol was compared in terms of radiation dose calculation between DSCT (6.5 ± 2.9 mSv) and SSCT (6.2 ± 1.0 mSv) scanners and no significant difference was noted (p = 0.99). However, the effective dose was significantly lower with DSCT (18.2 ± 8.3 mSv) than with SSCT (28.3 ± 7.0 mSv) in the retrospective gated protocol. Conclusions Prospective ECG-triggered CCTA reduces radiation dose significantly compared to retrospective ECG-gated CCTA, while maintaining good image quality.